Stability-guided treatment of pediatric radial neck fractures: percutaneous reduction with cast immobilization versus elastic intramedullary nailing - Yang, Yu-hao; Zou, Min-cheng; Liu, Wen-dong; Mao, Yun-peng; Sun, Jing-xuan; An, Rong; Liu, Ya; Wang, Xiao-dong; Zhang, Fu-yong (Frontiers in Pediatrics, 2026)
PurposeThe aim of this study was to evaluate the safety and efficacy of using intraoperative fracture stability as the primary criterion for selecting cast immobilization over internal fixation following percutaneous reduction of pediatric radial neck fractures.MethodsThis retrospective cohort study, conducted in strict compliance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines, analyzed data from 126 skeletally immature patients treated at a tertiary pediatric trauma center between 2017 and 2024. The cohort included two distinct treatment groups: 56 cases managed with PKWLR-CI and 70 cases treated with PKWLR-EIMN.ResultsThe two cohorts demonstrated comparable baseline angulation (42.3° ± 8.1 vs. 44.7° ± 9.6, p = 0.106) and equivalent 1-month angular loss (2.8° ± 1.4 vs. 3.1° ± 1.6, p = 0.569). The PKWLR-CI group exhibited greater operative efficiency (29 ± 6 vs. 47 ± 9 min, p < 0.001), shorter hospitalization (3.1 ± 0.7 vs. 4.3 ± 1.2 days, p = 0.002), and 38% lower direct costs (based on Diagnosis-Related Group reimbursement analysis). Both groups achieved excellent Mayo Elbow Performance Index (MEPI) scores (94.2 ± 5.1 vs. 92.7 ± 6.3, p = 0.215).ConclusionsIn this retrospective study, PKWLR-CI was associated with clinical outcomes that were comparable to those of PKWLR-EIMN for Metaizeau-Judet type II-IV fractures when intraoperative stability criteria are met. In this cohort, the selective use of PKWLR-CI avoided the need for implant removal surgeries and was associated with a 38% reduction in operative time and a 28% reduction in hospitalization costs, highlighting the critical role of periosteal hinge integrity in maintaining reduction.